Konseling Teman tentang Keterampilan Reproduksi Kesehatan Remaja - Kustin, Kustin; Handayani, Yuni (Jurnal Kesehatan Komunitas, 2024)
ABSTRACT Background: Adolescence is the period of change in an individual from childhood to adulthood that occurs in several changes, which are biological, psychological, and social changes. In general, today’s Indonesian teenagers are experiencing vulnerability to health problems and threats, especially sexual, free sex, and reproductive health problems. The existence of the Information and Counseling Center is to meet the needs of adolescents with information on reproductive health and sexuality without hesitation and embarrassment because they will get the information from peer relations through peer counseling. Methods: The population used was the students of the Plus Miftahul Ulum Kalisat Jember junior high school, a total of 80 students. The design of this study used a quasi-experiment with a non-equivalent control group pre-and post-test. The variables measured are knowledge, attitudes, and skills of adolescents related to reproductive health. Data was collected using questionnaires and observation sheets.  Results: The results of statistical tests using linear regression obtained peer counseling values for knowledge (p=0.000; R=0.254), attitudes (p=0.000; R square=0.432), and skills (p=0.000; R square = 0.191). Conclusion: Peer counseling can increase knowledge, attitudes, and skills in junior high school girls as well as drug and drug abuse. Hopefully, the school will continue to collaborate with health education institutions or services to continue the improvement of the abilities of counselors who attend peer counseling